IMPACT OF EGG SHELL AND SPOTS COLOUR ON THE QUALITY OF HATCHING EGGS DERIVED FROM THREE LINES OF LOCAL QUAIL - Ahmed, L. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was carried out to analyze the impact of lines, egg shell colour and intraction between (Line ⁎ eggshell colours) on egg quality characteristics and hatching parameters assess the correlation between these traits in three local quail eggs (desert, brown and white). A total of 409 eggs were collected from female quails during 16 weeks divided into five groups on the basis of eggshell colour and spot colour for each line. The results revealed that there were significant (P≤0.05) variances among lines for quality characteristics of the whole egg (weight, length, width, Egg volume, Haugh unit), albumen (weight, height, diameter), yolk (weight, height, index, Yolk/albumen) and shell (weight, thickness, egg surface area, unit surface). The desert line resulted in the best quality. The results demonstrated that internal and external egg quality characters were differed significantly among egg shell colour. Whereas, yolk parameters such as: yolk weight, yolk height, Yolk diameter and Yolk percentage revealed no significance differences among these groups. Phenotypic correlation appeared that there were significant correlation coefficients among the internal and external egg quality traits. The incubation characteristics, fertility, hatchability of fertile eggs, hatchability of set eggs and Chick hatching weight were significantly differences among eggshell colour groups within lines.